Penggunaan Dandelion (Taraxacum officinale) dalam Pakan Terhadap Performa Kalkun (Meleagris gallopavo): Utilization of Dandelion (Taraxacum officinale) in the Diet on Turkey (Meleagris gallopavo) Performance - H D S Tadjudin; M Shofiah Shofiah; S Aini Aini; widya hermana; Arif Darmawan (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2020)
The aim of this study was to evaluate fresh dandelion leaves on turkey performance. The study used a complete randomized design of 4 treatments and 6 replications. A total number of 24 turkeys (Meleagris gallapavo)-12 week-old were used in this 5 weeks of feed trial. The experimental animals were fed with the diet containing 37% of commercial broiler starter diet, 40% rice bran and forage (water hyacinth and fresh dandelion leaves). The treatments with fresh dandelion leaves addition were P0: 0%, P1: 5%, P2: 10%, and P3: 15%. The variables observed were bio active compound in dandelion leaves, daily behavior and turkey performance. Data were analyzed by Analysis of Variance (ANOVA) and the significant differences between treatments were analyzed by Duncan's Multiple Range Test. The results showed that dandelion leaves contain flavonoids, tannins, saponins and steroids, vitamin D were 17.37 ppm and antioxidants IC50 have an antioxidant activity with a value of 102.31. Observation of daily behavior showed that turkeys behavior was dominated by eating and resting activities, where the highest frequency of resting activities was 0.43 per second (P0). Turkey performance were not significantly different on feed consumption, carcass weight, carcass percentage for all treatments but significantly different (p<0.05) on average daily gain (AVG) and feed conversion ratio. Therefore it can be concluded that fresh dendelion leaves are able to used up to 15% in turkey diet. Key words: antioxidant, dandelion, turkey performance, vitamin D DAFTAR PUSTAKA Azhari NT & Apliriana E. 2016. Peranan jombang (Taraxacum officinale) sebagai hepatoprotektor. Jurnal Majority. 5(5): 32-36. Astuti S. 2008. Isoflavon kedelai dan potensinya sebagai penangkap radikal bebas. Jurnal Teknologi Industri dan Hasil Pertanian. 13(2): 126-136. Adawiah, Sukandar D & Muawanah A. 2015. Aktivitas antioksidan dan kandungan komponen bioaktif sari buah namnam. Jurnal Penelitian dan Pengembangan Ilmu Kimia. 1(2): 130-136. Amin M, Sawhney SS & Jassal MMS. 2013. Qualitative and quantitative analysis of phytochemicals of Taraxacum officinale. Wudpecker Journal of Pharmacy and Pharmocology. 2(1):1-5. Badarinath A, Rao K, Chetty CS, Ramkanth S, Rajan T & Gnanaprakash K. 2010. A review on in vitro antioxidant methods: comparisons, correlations and considerations. International Journal of Pharmatical Technology Research. 2(2): 1276-1285. Cook R, Xin H & Nettleton D. 2005. Effects of cage stocking density of feeding behaviours of groups housed laying hens. Journal Animals Agriculture Biology. 49(1): 187-192. Dheer R & Bhatnager P. 2010. A study of the antidiabetic activity of Barleria prionitis linn. Indian Journal of Phamacology. 42(2): 1-5. Gibril S, Samsel S RM, Yassin OE, Hassan AA & Atta M. 2013. Body gain and carcas charateristics of turkeys (Meleagris gallopavo) under extensive system of management in the student. International Journal of Applied Poultry Research. 2(2): 23-26. Mishra A, Kaone P, Schouten W, Sprujit B & Metz J. 2005. Tempral and sequential structure of behaviour and facility usage of laying hens in an encrihed environment. Poultry Science. 84:979-991. Rizky A, Haryono D & Kasymir. 2016. Analisis usaha dan strategi pengembangan ternak kalkun mitra alam kabupaten pringsewu provinsi Lampung. Jurnal Ilmu Ilmu Agribisnis. 4(3): 235-242. Ramian F & Indrianti MA. 2018. Analisa potensi eceng gondok (Eichornia crassipes) Danau Limboto sebagai pakan ternak. Prosiding Seminar Nasional Integrated Farming System. Gorontalo (ID): Universitas Muhammadiyah Gorontalo. Setiawan B. 2017. Kandungan protein kasar dan serat kasar dedak padi yang difermentasi dengan mikroorganisme lokal [skripsi]. Makassar (ID): Universitas Hasanuddin. Steel RGD & Torrie JH. 1993. Prinsip dan Prosedur Statistika Suatu Pendekatan Biometrik. Sumatri B, penerjemah. Terjemah dari: Principles and Procedures of Statistics. Jakarta (ID): Gramedia Pustaka Utama, Suprijatna E, Sunarti D, Mahfudz L D, Ardiningsasi S M, Inayah A & Purnomo A H S. 2010. Performans produksi dan efisiensi penggunaan protein ransum pada kalkun lokal yang dipelihara secara intensif diberi ransum mengandung daun kobis (Brassica oleracea var capitata) afkir. Seminar Nasional Unggas Lokal. Semarang (ID): Fakultas Peternakan, Universitas Diponegoro. Wulan, Yudistira A, & Rotinsulu H. 2019. Uji aktivitas antioksidan dari ekstrak etanol daun Mimosa pudica Linn. menggunakan metode DPPH. Jurnal Ilmiah Farmasi. 8(1): 106-113.